"First and Foremost They're Survivors": Selective Manipulation, Resilience, and Assertion Among Prostitute Women. (October 2015) - Shdaimah, Corey S.; Leon, Chrysanthi
Based on qualitative data from three sites ( N = 76), we describe prostitute women's agency and problematize dominant assumptions. Prostitute women exhibit creative, resilient, and rational conduct. Rejecting victimhood, our respondents demonstrate moral reasoning, make choices, work systems that dominate their lives, and assert power and control when they can. Their resistance, while serving a symbolic function, also expresses their system savvy and self-advocacy that produce measurable benefits. We distinguish between "being manipulative" and context-specific ethical conduct intended to further their survival.